Noetic Experience and the Morphology of Prayer: Evagrius Ponticus and the Greek Philosophical Tradition - JUGRIN, Daniel (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2025)
This article examines the role of prayer within the spiritual framework of Evagrius Ponticus, focusing particularly on his definitions and his significant notion of “pure prayer.” It aims to elucidate the nature and key function of this form of prayer within his ascetic and contemplative vision. By conducting a thorough textual analysis of Evagrius’s key writings and spiritual terminology, the study places his teachings within the historical context of early Christian spirituality and its engagement with Greek philosophical ideas. The article contends that Evagrius’s perspective of prayer as the preeminent function and genuine “state” of the intellect (nous) emphasizes the originality and relevance of his “imageless prayer” theory, positioning it as a central element in his mystical system.